Female Subjectivity through Body Dressing and Positioning in Malaysian Advertisements - Peng, University of Malaya, Malaysia, Su Soon (Asiatic: IIUM Journal of English Language and Literature, 2016)
Most feminist studies on the topics of dress and the female body have been carried out within the context, as well as from the perspective, of the West. Malaysia as a multiethnic country that is at the same time open and exposed to the effects of globalisation offers an interesting case study on the representations of diverse women’s imagemaking and their implications on gendered subjectivity and selfhood. Body dressing and positioning are among the powerful means of representation that construct the subject in a way that furthers the self-advantaging ends of the advertiser. Dress and body-related texts are excerpted from Malaysian print advertisements in selected English dailies for close semiological and discourse analysis in the context of the dominant twin ideologies of patriarchy and Islam. Drawing on a broad feminist theory, the analysis reveals two diametrically opposite overarching themes of oppression and empowerment. Discussion related to these themes addresses the Malaysian context of cultural norms of fashion discourses and the underpinning economic motivation.